ANALISIS POLA PENDIDIKAN EKONOMI DALAM KELUARGA PADA SISWA SMA NEGERI 1 KAYAN HULU - Bernadeta Lilis (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study aims to describe the pattern of economic education in students' families and the obstacles faced in internalizing economic education in students' families at SMA Negeri 1 Kayan Hulu. This study uses a qualitative approach with a phenomenological research design. Data collection techniques used by interviews and observations. The data validity technique uses source triangulation and technical triangulation. The data analysis technique used is the interactive analysis of Miles and Huberman with the stages of data reduction, data display, and conclusion drawing/verification. Informants in this study were parents and children of students at SMA Negeri 1 Kayan Hilir. The results showed that parents of students applied family economic education through habituation, example, explanation and giving rules and punishments. In addition, parents also teach children to manage finances wisely and introduce the work they are engaged in by teaching children to participate while working. The pattern of economic education carried out varies, including the pattern of democratic education and the pattern of authoritarian education. The obstacles faced by parents in internalizing economic education in the family include differences of opinion in terms of consumption patterns, the tendency of children today to be more wasteful, and lazy to help parents work because children prefer to play